ANALISIS VALUE FOR MONEY DALAM MENINGKATKAN KUALITAS PELAYANAN PT. POS INDONESIA (Persero) KABUPATEN SUKOHARJO - Chintya Noer Cahyani; Dinara Kharisma Sari; Maya Widyana Dewi (Jurnal Akuntansi dan Pajak, 2024)
The aim of this research is to determine the effect of value for money with economic, efficiency and effectiveness elements on the quality of public services at PT. Pos Indonesia (Persero) Sukoharjo Regency. This research is quantitative research. The sample was 50 respondents. Data collection techniques through surveys by distributing questionnaires to the intended respondents. Data analysis methods include descriptive statistical analysis, validity tests, reliability tests and classical assumption tests. The research results show that 1) economic, efficiency and effectiveness elements simultaneously as value for money elements influence the quality of PT's public services. Pos Indonesia (Persero) Sukoharjo Regency 2) partial economic elements as one of the value for money elements have no effect on the quality of PT's public services. Pos Indonesia (Persero) Sukoharjo Regency 3) partial efficiency elements as an element of value for money have no effect on the quality of PT's public services. Pos Indonesia (Persero) Sukoharjo Regency, and 4) the partial effectiveness element as one of the value for money elements influences the quality of PT's public services. Pos Indonesia (Persero) Sukoharjo Regency.